18F-FDG PET/CT for Identifying the Potential Primary Diseases and Predicting Prognosis of Secondary Hemophagocytic Lymphohistiocytosis in Children. (16th April 2022) - Wei, Ang; Lu, Xia; Ma, Honghao; Lian, Hongyun; Yang, Xu; Zhang, Liping; Wang, Dong; Chen, Sitong; Zhang, Qing; Li, Zhigang; Zhang, Rui; Yang, Jigang; et al.
Abstract : Hemophagocytic lymphohistiocytosis (HLH) is a rare, potentially fatal illness, which can be divided into primary HLH (pHLH) and secondary HLH (sHLH). pHLH can be driven by genetic defections. Moreover, the sHLH is usually be triggered by malignancy or non-malignancy diseases. Sixty-two newly diagnosed sHLH patients with known etiology and those who underwent 18 F-FDG PET/CT examination from July 2018 to December 2020 were retrospectively analyzed. They were divided into malignancy-associated HLH (M-HLH, n  = 13) and non-malignancy-associated HLH (NM-HLH, n  = 49). The metabolic parameters of the liver (Li), spleen (Sp), bone marrow (BM), lymph nodes (LN), and their ratios to the liver background (LiBG) and mediastinum (M) were compared between two groups. These metabolic parameters were evaluated for correlation with laboratory parameters and prognostic parameters. We found that the SUVmax -LN/Sp/Li and SUVmean -Sp in M-HLH were significantly higher than those in NM-HLH (P = 0.031, 0.035, 0.016,  and  0.032 ). The malignant disease should be considered when SUVmax-LN was higher than 4.41 (sensitivity 61.5%, specificity 81.6%). Hypermetabolic lesions in extranodal organs were more likely to occur in M-HLH than in NM-HLH (P = 0.011 ). IFN- γ was positively correlated with SUVmax-BM/Li/Sp and SUVmean-BM/Li/Sp (P < 0.05 ). Ferritin, sCD25, IL-6, and IL-10 were positively correlated with SUVmax-Sp and SUVmean-Sp (P < 0.05 ). In Epstein–Barr virus-associated HLH (EBV-HLH), the SUV parameters of bone marrow were significantly correlated with a poor 2-week treatment response, overall survival, and event-free survival (P < 0.05 ). We conclude that some 18 F-FDG PET/CT metabolic parameters can help identify the etiology of sHLH in children and provide directions for further inspection. The malignant disease should be considered when the SUVmax-LN is higher than 4.41 and hypermetabolic lesions occur in extranodal organs. In EBV-HLH, a higher SUV of bone marrow is associated with a poorer prognosis.